AB0566 Arthritis in Systemic Vasculitis: A Retrospective Analysis. (10th June 2014) - Carbonella, A.; Berardi, G.; Gremese, E.; Bosello, S.L.; Petricca, L.; Parisi, F.; Zoli, A.; Ferraccioli, G.
Abstract : Background: Few data are available on the prevalence of arthritis in vasculitides. Objectives: To evaluate the prevalence and the features of arthritis in our cohort of patients with systemic vasculitis. Methods: Data were collected from 206 patients with systemic vasculitides referred to our center from 2008 to 2013, excluding the cases of overlap between vasculitis and definite inflammatory arthritis. Of the 206 patients (mean age 58.0±16.7 years, 65.5% females), 105 had large vessel vasculitis (64 Giant cell arteritis, 24 Aortitis and Periaortitis, 10 Takayasu, 7 Central Nervous System Vasculitis), 101 had small-medium vessel vasculitis (36 Granulomatosis Polyangiitis (GPA), 20 Microscopic polyangitis (MPA), 14 Eosinophilic granulomatosis Polyangiitis (EGPA), 12 Cryoglobulinemic vasculitis, 10 Panarteritis nodosa (PAN), 4 ANCA-positive vasculitis, 3 Shonlein Henoch purpura and 3 gastrointestinal vasculitis). We performed a clinical, laboratoristic and radiological evaluation. Results: Twenty-five out of 206 (12.1%) had arthritis. All 25 patients had small-medium vessel vasculitis (28% (7/25) GPA, 20% (5/25) MPA, 16% (4/25) Cryoglobulinemic syndrome, 16% (4/25) EGPA, 12% (3/25) Henoch-Shonlein purpura, 8% (2/25) PAN). None of the patients in the group of large-vessel vasculitis had arthritis. We observed 14 cases of oligoarthritis, 10 of poliarthritis and only 1 case of monoarthritis. The most frequently involved joint was the ankle. Nineteen patients developed arthritis at the onset of vasculitis, 4 patients had arthritis before vasculitis and only 2 patients had arthritis during vasculitis flares. None had radiographic erosions at X-ray. Nine of 25 patients performed ultrasound which showed capsular distension, tenosynovitis, synovitis with low grade or absent Power Doppler positivity. We divided patients suffering from small-medium vessel vasculitis into two groups: arthritic patients (25) and patients without arthritis (76). The two groups had the same demographics (age and sex) and laboratoristic (ESR increasing, CPR increasing, ANCA positivity, Rheumatoid Factor (RF) positivity, complement reduction) features. The only difference between the two groups was the cutaneous involvement: purpura appeared in 64% (16/25) of patients with arthritis vs 34.2% (26/76) of patients without arthritis (p=0.01). Arthritis had a good clinical response to therapy for vasculitis and it did not reappear during vasculitis flares. Conclusions: Arthritis is a possible manifestation of systemic vasculitis, particularly of small-medium vessel vasculitis, usually occurring at the disease onset. It is usually oligoarticular and non-erosive, showing the same incidence in males and females. It seems to be associated with cutaneous involvement while no association with ANCA antibodies or RF was seen. Arthritis shows a good response to vasculitis treatment and it does not recur during vasculitis flares. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4954